Investigation of surface roughness in machining of aluminum alloy with EDM - Kasman, Şefika; Tosun, Nihat (My University, 2014)
In this study, the relationship between surface roughness of workpiece and process parameters and was investigated for AA7075 aluminum alloy with electrical discharge machining (EDM). Experiments were conducted under different process parameters, namely, current, pulse on-time, pulse off-time, gap voltage and electrode material. The settings of machining parameters were determined by using Taguchi experimental design method. The level of importance of the machining parameters on the performances characteristics is determined by using analysis of variance (ANOVA). The optimum machining parameters combination was obtained by using the analysis of S/N ratio
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: EDM; Surface roughness; Aluminum; ANOVA